Chimeric tumor necrosis factor receptors with constitutive signaling activity. - Bazzoni, F (1995)
Many hormone and cytokine receptors are crosslinked by their specific ligands, and multimerization is an essential step leading to the generation of a signal. In the case of the tumor necrosis factor (TNF) receptors (TNF-Rs), antibody-induced crosslinking is sufficient to trigger a cytolytic effect. However, the quaternary structural requirements for signaling--i.e., the formation of dimers, trimers, or higher-order multimers--have remained obscure. Moreover, it has not been clear whether the 55-kDa or 75-kDa TNF-R is responsible for initiation of cytolysis. We reasoned that an obligate receptor dimer, targeted to the plasma membrane, might continuously signal the presence of TNF despite the actual absence of the ligand. Such a molecule, inserted into an appropriate vector, could be used to project receptor-specific "TNF-like" activity to specific cells and tissues in vivo. Accordingly, we constructed sequences encoding chimeric receptors in which the extracellular domain of the mouse erythropoietin receptor (Epo-R) was fused to the "stem," transmembrane domain, and cytoplasmic domain of the two mouse TNF-Rs. Thus, the Epo-R group was used to drive dimerization of the TNF-R cytoplasmic domain. These chimeric proteins were well expressed in a variety of cell lines and bound erythropoietin at the cell surface. Both the 55-kDa and the 75-kDa Epo/TNF-R chimeras exerted a constitutive cytotoxic effect detected by cotransfection or clonogenic assay. Thus, despite the lack of structural homology between the cytoplasmic domains of the two TNF-Rs, a similar signaling endpoint was observed. Moreover, dimerization (rather than trimerization or higher-order multimerization) was sufficient for elicitation of a biological response.